Understanding the characteristics of recurrent visits to the emergency department by paediatric patients: a retrospective observational study conducted at three tertiary hospitals in Korea. Issue 2 (16th February 2018) - Kim, Byung-Soo; Kim, Jung-Youn; Choi, Sung-Hyuk; Yoon, Young-Hoon
Abstract : Objectives: The number of paediatric patients visiting the emergency department (ED) continues to rise. In South Korea, approximately 25% of the patients who visit the ED are paediatric patients. In the USA, about 20% of the paediatric population were found to have visited the ED in the past year. A recent study demonstrated that 4.5%–8% of patients account for 25% of all ED visits. Therefore, the aim of this study was to identify the characteristics of recurrent visits. Methods: Design: retrospective observational study. Setting: this study examined and analysed medical record data involving three tertiary EDs. Participants: a total of 46 237 ED visits by patients <16 years during 1-year period. Main outcome measures: data collected included the number of recurrent ED patients, frequency of recurrent visits, age, sex, insurance status, period until recurrent visit (days), main diagnosis and ED discharge results. Results: Excluding patients with multiple visits, the total number of paediatric patients who fit the study criteria was 33 765. Among these patients, 23 384 (69.2%) had no recurrent ED visits in the subsequent year after their first visit. A total of 15 849 (46.8%) patients were toddlers (between age 1 and 4 years). In the patient group without a recurrent visit, fever was the most common diagnosis. Conclusions: Our study reviewed medical records to inspect the characteristics of patients who return to care. Higher recurrent visit frequency was associated with using the 119 rescue centre service, having a medical condition, with younger age and a higher rate of hospitalisation. Analysis of the factors associated with frequent ED visits will help to improve care for paediatric patients who visit the ED.